Green supply chain management practices and environmental performance: a study of employees practices in Malaysia chemical related industry - Jaaffar A.H.; Kaman Z.K. (Dorma Journals, 2023)
As one of emerging and developing country, Malaysia is under pressure to reduce energy consumption and carbon emissions. Companies especially those with high hazardous wastes production need to ensure that their wastes are improperly treated, stored, transported or disposed off or managed in order to minimize it impact to environment. In view of this, Green Supply Chain Management (GSCM) is important in influencing the total environment impact of any companies involved in supply chain activities as well as contribute to sustainability performance enhancement. This study aims to examine the employees insight from Malaysia Chemical Related Industry on their firms green supply chain management practices and environmental performance. Based on the theoretical framework of green supply chain management practices, an empirical study of the green supply chain management practices and environmental performance was conducted. Out of the five variables of green supply chain management practices, only the legislation and regulation have positive significant relationship with environmental performance. This result shows that most employees consider that their firms environmental performance will be improve by complying with the legislation and regulation rather than proactively develop green supply management practices. 2020, Dorma Journals. All rights reserved.